О линиях уровня гладких функций - Г. А. Сукиасян (Հայաստանի ԳԱԱ)
С помощью ранее установленного метода оценки длин линий уровня действительных функций доказывается теорема, которая является аналогом второй основной теоремы теории Г-линий, которая, в свою очередь, является аналогом второй основной теоремы Р. Неванлинны. Based on the earlier established general estimation method of the lengths of level sets of real functions, the paper proves a theorem which is an analog of the second fundamental theorem of the theory of ¡-lines which, in its turn, is an analog of the second fundamental theorem of R. Nevanlinna.
Keywords: Mathematics; Science